Berdaya Lingkungan Berkelanjutan: Inovasi Konsep 3R Untuk Pemanfaatan Sumber Daya Daur Ulang di Dusun Bleder Ngadiharjo - Marlina Kurnia; Fatma Dianita; Nurul Aulia Sajida; Ardia Dewi Febriani; Aprilia Finanda; Nur Fauzan (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
The Final Report of the Community Service Program (PPMT) in Bleder Ngadiharjo Hamlet implements the innovation of the 3R concept (Reduce, Reuse, Recycle) to strengthen the utilization of recycled resources. By involving active participation of the local community, the program aims to enhance environmental awareness and skills in waste management. Through educational approaches and training, the activities promote sustainable practices in waste management and reduction. Program evaluation indicates a significant improvement in waste management efficiency and creative waste utilization. Collaboration among various stakeholders, including local institutions and communities, is key to the success of the program. Thus, the PPMT in Bleder Ngadiharjo provides a sustainable positive impact on the community and the surrounding environment, while promoting awareness of the importance of sustainable practices in daily life.